THE EFFECTS OF ETHANOL EXTRACT AND ETHYL ACETATE FRACTIONATION OF SECHIUM EDULE JACQ. SWARTZ ON TRIGLYCERIDE LEVELS IN MALE RATS WITH TYPE 2 DIABETES MELLITUS - Siahaan, Jekson Martiar; Julianto, Endy; Silitonga, Hendrika Andriana (Indonesian Journal of Medicine, 2019)
Background: The prevalence of diabetes mellitus (DM) from year to year is increasing. Hyperglycemia that occurs in DM is caused by oxidative stress that damages pancreatic ? cells. This situation can be controlled with synthetic hypoglycemic drugs, but it requires high medical costs. Therefore, alternative therapies that are easily available, relatively inexpensive, have potential anti-hypoglycemia and anti-cholesterolemia which is found in conjoined flasks (Sechium edule (Jacq.) Swartz) which contains flavonoids are needed. The purpose of this study was to analyze the effectiveness of ethanol extract and fractionation of ethyl acetate extracts of Sami (pumpkin) (Sechium edule (Jacq.) Swartz) as anti-hipoglycemia and anti-hypertriglycerides in white male wistar rats (Rattus novergius sp.) induced by STZ-NA-HFDD.Subjects and Method: A randomized controlled trial was conducted to assess the effectiveness of ethanol extract and fractionation of pumpkin fruit ethyl acetate extract. The sample included white male wistar rats (Rattus novergius sp.) Hyperglycemia induced by STZ-NA-HFD. The dependent variable was triglyceride levels. The independent variables were administration of ethanol extract and fractionation of pumpkin fruit ethyl acetate extract.Results: Ethyl acetate fraction 45 mg/kgBW better reduce triglyceride levels but statistically does not have significant differences between groups.Conclusion: The group that received Metformin and the group that was given ethanol extract 45 mg/kgBW had lower triglyceride levels compared to the other therapy and control groups.Keywords: Hipertrigliseridemia, diabetes mellitus, STZ-NA-HFDCorrespondence: Jekson Martiar Siahaan. Department of Physiology, Faculty of Medicine, Universitas Methodist Indonesia. Jl. Setia Budi Pasar II Tj. Sari, Medan 20132, North Sumatera. Email: Jekson.siahaansked@gmail.comIndonesian Journal of Medicine (2019), 4(4): 371-375https://doi.org/10.26911/theijmed.2019.04.04.10